2020
DOI: 10.3389/fendo.2020.00023
|View full text |Cite
|
Sign up to set email alerts
|

Higher Blood Urea Nitrogen and Urinary Calcium: New Risk Factors for Diabetes Mellitus in Primary Aldosteronism Patients

Abstract: The aim of the study was to investigate the prevalence and risk factors of diabetes mellitus (DM) in primary aldosteronism (PA) patients.Methods: This case-control study enrolled 259 PA patients in West China Hospital, China from January 2016 to January 2019. Patients were divided into three groups: PA group, PA + impaired fasting glucose (IFG)/impaired glucose tolerance (IGT) group and PA + DM group. Clinical characteristics (like age and sex) and laboratory variables (like plasma aldosterone concentration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“… 37 Meanwhile, patients with primary aldosteronism were reported to be more likely to have DM due to increased UN levels resulting from impaired renal function, relative to the general population. 38 A study in China by Feng et al that included 13,448 eligible pregnant women, of which 2,793 had GDM, reported that elevated UN levels in early pregnancy were positively and dose-responsively correlated with an increased risk of GDM. 22 However, we detected no association between UN and GDM in either our total population or age-stratified subgroups.…”
Section: Discussionmentioning
confidence: 99%
“… 37 Meanwhile, patients with primary aldosteronism were reported to be more likely to have DM due to increased UN levels resulting from impaired renal function, relative to the general population. 38 A study in China by Feng et al that included 13,448 eligible pregnant women, of which 2,793 had GDM, reported that elevated UN levels in early pregnancy were positively and dose-responsively correlated with an increased risk of GDM. 22 However, we detected no association between UN and GDM in either our total population or age-stratified subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarded hypokalemia as a risk factor for DM. They thought that hypokalemia may decrease insulin secretion and induce insulin resistance, followed by dysbiosis of glucose metabolism (36). We found that Romboutisa and Bacteroides were more abundant in PA patients than in primary hypertension patients.…”
Section: Discussionmentioning
confidence: 57%
“…Of which Insulin resistance, a condition where cells become resistant to the effects of insulin and is often found in obesity, T2DM, non-alcoholic fatty liver disease, etc. [ 49 51 ]; for PPAR signaling pathway, which plays significantly in inflammation, insulin sensitivity, lipid metabolism, as well as the expression of hepatic enzymes regulating glucose homeostasis [ 52 , 53 ]; for FoxO signaling pathway, which controls important physiological events, including apoptosis, glucose metabolism, oxidative stress resistance, by converting the external stimuli of insulin, growth factors, cytokines, and oxidative stress into cell-specific biological responses by regulating the transcriptional activity of target genes [ 54 , 55 ]; for Fc epsilon RI signaling pathway, which contributes to inflammatory responses by regulating mediators and cytokines [ 56 , 57 ]; there are also pathways that influence diabetes primarily by regulating metabolism, such as cAMP signaling pathway [ 58 ], AMPK signaling pathway [ 59 ], Starch and sucrose metabolism [ 60 ], Carbohydrate digestion and absorption [ 61 ], Aldosterone-regulated sodium reabsorption [ 62 ], Adipocytokine signaling pathway [ 63 ]; and other T2DM directly related pathways like Insulin signaling pathway, and Type II diabetes mellitus, are involved. In addition, combined with literature search, the corresponding symptoms of these pathways were synthesized to construct the "herbs-targets-pathways- symptoms" network, which represents a global view of GQWTF in treating T2DM, with their pathways that functions and related possible symptomatic improvement.…”
Section: Discussionmentioning
confidence: 99%